Financial Literacy and the Sustainability of Rural SMEs in Nepal: Examining the Mediating Effects of Access to Finance and Risk Attitude - Khanal, Rajiv (NPRC Journal of Multidisciplinary Research, 2025)
This study investigates how financial literacy impacts the sustainability of small and medium enterprises (SMEs) in rural Nepal. It specifically examines whether access to finance and the owners’ financial risk attitude act as mediating mechanisms in this relationship. A structured questionnaire was used to collect data from 403 SME owners in Lumbini and Gandaki provinces. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software to test the direct and mediating relationships. The results show that financial literacy has a direct positive effect on SME performance. Furthermore, it strongly improves both access to finance and financial risk attitudes. A key finding is that while financial risk attitude is a significant mediator, access to finance is not. This means that getting loans alone does not automatically lead to better SME performance; what matters more is the owners’ knowledge and their willingness to take calculated risks. For policymakers and banks, the findings suggest that simply improving loan access is insufficient. Support programs should instead prioritize providing basic financial education for rural SME owners. Training should focus on budgeting, saving, prudent loan use, and risk management to build a foundation for sustainable business practices. This study is one of the first in rural Nepal to develop and test an integrated model that includes financial literacy, access to finance, and risk attitude simultaneously. It provides new evidence on the limited direct role of finance access and highlights the critical importance of risk attitude as a pathway to SME sustainability.